Digital diaspora : a race for cyberspace - Everett, Anna, 1954- (SUNY Press, 2009)
Traces the rise of black participation in cyberspace, particularly during the early years of the Internet. The author challenges the problematic historical view of black people as quintessential information-age outsiders or poster children for the digital divide by uncovering their early technolust and repositioning them as eager technology adopters and consumers, and thus as co-constituent elements in the information technology revolution. Offers case studies that include lessons learned from early adoption of the Internet by the Association of Nigerians Living Abroad and their Niajanet virtual community, the grassroots organizing efforts that led to the Million Woman March, the migration of several historical black presses online, and an interventionist critique of race in contemporary video games.
Keywords: Computers -- Social aspects -- United States.; African Americans and mass media -- United States.; Digital media -- Social aspects -- United States.; African diaspora.; Ordinateurs -- Aspect social -- États-Unis.; Noirs américains et médias -- États-Unis.; Médias numériques -- États-Unis -- Aspect social.; Africains -- Pays étrangers.; COMPUTERS -- Social Aspects -- General.; African Americans and mass media; African diaspora; Computers -- Social aspects; Digital media -- Social aspects; United States; Digitale Spaltung; Internet; Massenmedien; Schwarze; USA; Schwärze; Gesellschaft.; Digitale Spaltung.; Digitale Medien.; Schwarze.; USA.; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies